Study of Strontium Titanate and Barium Zirconate Properties Using Molecular Dynamics Simulation - Goh, Wen Fong (2013)
Molecular dynamics simulation has been carried out on strontium titanate and barium zirconate in order to study the microscopic atomic behavior, and the macroscopic thermodynamic and thermal transport properties of the perovskite materials. The intricate interatomic potentials can be simplied into pairwise interactions, which consist of ionic interaction, short-range repulsion, Van der Waals attraction and Morse covalent bonding. New sets of potential parameters of strontium titanate and barium zirconate have been presented. Radial distribution functions have been obtained to study the atomic and structural behavior. Structural parameters, thermal expansion coecient, isothermal compressibility, heat capacity and thermal conductivity have been evaluated in the temperature range of 298 - 2000 K and pressure ranging from 1 atm to 20.3 GPa. At room temperature, the values of lattice parameters of strontium titanate and barium zirconate are obtained to be 3.9051 A and 4.1916 A. While the calculation of thermal expansion coecients of strontium titanate and barium zirconate gives 1.010 10